(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article provides a theoretical and analytical examination of child upbringing in the context of globalization and digital transformation, focusing on the role of the dopamine system in the psychophysiological development of younger generations and on patterns of digital behavior within the framework of Generations Zeta, Alpha, and Beta. Contemporary information threats in cyberspace, the influence of short-form content (Reels, Shorts), and the impact of internet trolling on the consciousness of young people are analyzed as interconnected phenomena. The study also offers practical recommendations aimed at strengthening socio-spiritual security through the promotion of the concept of the “Uzbek National Spirit” and increasing parental responsibility in the digital age